Pengaruh Edukasi Perawatan Kaki terhadap Pencegahan Diabetic Foot Ulcer pada Pasien Diabetes - Emeliawati; Sriyati, Sriyati; Widiastuti, Widiastuti (STIKES Suaka Insan, 2025)
Diabetes mellitus is a disease with increasing prevalence, with diabetic foot ulcer as one of the main preventable complications. Diabetic foot ulcers can lead to lower limb amputation and are a major cause of morbidity and mortality in diabetic patients. This study aims to determine the effect of foot care education on knowledge of diabetic foot ulcer prevention in diabetes mellitus patients at PKU Muhammadiyah Hospital, Yogyakarta. The research method was a quasi-experimental pre-test post-test control group design. The sampling technique used the total sampling method with 30 respondents divided into an intervention group (15 people) and a control group (15 people). The research instrument was a questionnaire based on the Diabetic Foot Knowledge Scale (DFKS), which has been tested for validity and reliability. The results of the study with the paired sample t-test showed a p-value = 0.005 (<0.05), which indicated a significant effect of education on knowledge of diabetic foot ulcer prevention. Foot care education effectively increases the knowledge of diabetes mellitus patients in preventing diabetic foot ulcers in diabetes mellitus patients at PKU Muhammadiyah Hospital, Yogyakarta. This research is expected to serve as a reference for RS PKU Muhammadiyah Yogyakarta in developing policies and standard procedures related to the education and care of diabetes mellitus patients.